2010
DOI: 10.1007/s11064-010-0324-y
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Chondroitin Sulfate and Heparan Sulfate in the Developing Brain

Abstract: Chondroitin sulfate and heparan sulfate proteoglycans are major components of the cell surface and extracellular matrix in the brain. Both chondroitin sulfate and heparan sulfate are unbranched highly sulfated polysaccharides composed of repeating disaccharide units of glucuronic acid and N-acetylgalactosamine, and glucuronic acid and N-acetylglucosamine, respectively. During their biosynthesis in the Golgi apparatus, these glycosaminoglycans are highly modified by sulfation and C5 epimerization of glucuronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 87 publications
1
77
0
Order By: Relevance
“…This is due to normal expression of the other EXT protein, which still has glycosyltransferase activity although significantly less than the amount generated by the EXT1and EXT2 complex as the enzymes cannot substitute for one another during co-polymerisation 9 38–40. Therefore, while residual levels of heparan sulfate facilitate some cellular functions, they are not sufficient for proper neural development including brain morphology and midline axon guidance—processes defective in Ext-mutants 17 18. Collectively, these studies have demonstrated the importance of sufficient and spatiotemporal expression of heparan sulfate biosynthesis enzymes in the development of brain size and structure.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to normal expression of the other EXT protein, which still has glycosyltransferase activity although significantly less than the amount generated by the EXT1and EXT2 complex as the enzymes cannot substitute for one another during co-polymerisation 9 38–40. Therefore, while residual levels of heparan sulfate facilitate some cellular functions, they are not sufficient for proper neural development including brain morphology and midline axon guidance—processes defective in Ext-mutants 17 18. Collectively, these studies have demonstrated the importance of sufficient and spatiotemporal expression of heparan sulfate biosynthesis enzymes in the development of brain size and structure.…”
Section: Discussionmentioning
confidence: 99%
“…GAGs, like nucleic acids, are polyanions, and GAGs function in brain development and are critical determinants of brain structure and function (27)(28)(29)(30). The GAG heparan sulfate (HS) localizes at amyloid plaques in the brains of humans and animals with prion disease (31) and Alzheimer's disease (32), and HS is suggested to be involved in the pathogenesis of amyloidosis.…”
Section: Protein Misfolding Cyclic Amplification (Pmca) Is An In Vitrmentioning
confidence: 99%
“…Indeed, HSPGs stabilize the FGF ligand-receptor complex to promote FGF2 signaling [27, 35, 45, 67, 98, 122]. Proteoglycans can also regulate cell adhesion and cell migration through interactions with membrane proteins and other components of the ECM, including integrins, laminin, collagen, and fibronectin [70, 82]. In addition, proteoglycan intracellular functions are likely to contribute to NSPC regulation as they link extracellular signals with cytoskeletal organization and intracellular signaling [12, 33, 48, 81].…”
Section: Proteoglycan Regulation Of Neural Stem and Progenitor Celmentioning
confidence: 99%